2007
DOI: 10.1016/j.parco.2007.02.010
|View full text |Cite
|
Sign up to set email alerts
|

Virtual screening on large scale grids

Abstract: Large scale grids for in silico drug discovery open opportunities of particular interest to neglected and emerging diseases.\ud In 2005 and 2006, we have been able to deploy large scale virtual docking within the framework of the WISDOM\ud initiative against malaria and avian influenza requiring about 100 years of CPU on the EGEE, Auvergrid and TWGrid\ud infrastructures. These achievements demonstrated the relevance of large scale grids for the virtual screening by molecular\ud docking. This also allowed evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 30 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…For examples, the molecular modeling for drug discovery was demonstrated by the WISDOM (Wide In Silico Docking on Malaria) and Virtual Laboratory and Opal activities [8][9][10][11][12]. The Virtual Laboratory and Opal use Nimrod-G which has the advantage of the Globus Toolkit and web service description language (WSDL) file to implement the Grid service-based platform [8].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…For examples, the molecular modeling for drug discovery was demonstrated by the WISDOM (Wide In Silico Docking on Malaria) and Virtual Laboratory and Opal activities [8][9][10][11][12]. The Virtual Laboratory and Opal use Nimrod-G which has the advantage of the Globus Toolkit and web service description language (WSDL) file to implement the Grid service-based platform [8].…”
Section: Related Workmentioning
confidence: 99%
“…In the first large-scale EGEE Biomed Data Challenge on the Grid [9], DIANE was used as an alternative approach to WISDOM scripts to manage millions of docking jobs on the Grid [9,10]. To compare with the large-scale job submission scripts, it has been shown that using the masterworker job-pulling model and the automatic failure recovery mechanism built into DIANE, one can increase the overall efficiency by 38% [9].…”
Section: Dianementioning
confidence: 99%
See 1 more Smart Citation
“…For example, users from different parts of the world, including rural and remote areas, can utilize e-Infrastructures and have access to high-quality research resources, such as specialized instruments in bioinformatics or meteorological data for environmental sciences (Jacq et al, 2007). The availability of bandwidth has hampered African scientific communities from reaching similar benefits, but this is now rapidly changing as the UbuntuNet network's (AfricaConnect, 2014) interconnections unroll across the African continent.…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, the Wide In-Silico Docking of Malaria (WISDOM) project aimed to develop high throughput virtual screening docking-based in-silico drug discovery platforms for neglected and emergent diseases supported by Grid computing (Jacq et al, 2007;Breton et al, 2008). EELA has enabled Latin American countries to take part in global scientific data challenges and to propose related projects, both to the benefit of Latin American scientists.…”
Section: Introductionmentioning
confidence: 99%